AB0346 Investigation of alexithymia in patients affected by rheumatoid and psoriatic arthritis: cross-sectional observation. (12th June 2018) - Fonti, G.L.; Chimenti, M.S.; Conigliaro, P.; Hitaj, J.; Galluzzo, M.; Talamonti, M.; Kroegler, B.; Greco, E.; Perricone, R.
Abstract : Background: Rheumatoid arthritis (RA) and Psoriatic arthritis (PsA) are chronic inflammatory diseases that lead to an overthrow of articular structure, functional limitation and disability. Alexithymia is a personality trait characterised by deficits in cognitive processing and regulation of emotions. A broad association between alexithymia and symptoms as depression, inflammation and pain has been demonstrated. Objectives: to evaluate the prevalence of alexithymia in patients affected by Rheumatoid and Psoriatic arthritis. Methods: We prospectively enrolled, from January to December 2017, patients affected by RA diagnosed according to the ACR revised criteria and PsA diagnosed according to the CASPAR criteria referred to the out-patients clinic of the Rheumatology Unit of Policlinico Tor Vergata, Rome. The 20-item Toronto Alexithymia Scale (TAS-20) was used to assess alexithymia. Disease activity, function and quality of life, clinimetric tests as well as ESR and CRP were assessed. Statistical comparisons were performed using Pearson's Coefficient of Skewness, the unpaired t-Test and Mann-Whitney test. Results: A total of 50 RA patients and 51 PsA patients were enrolled (table 1). The TAS-20 score showed that 38.6% (39/101) of patients had alexithymia, 26.7% (27/101) patients were in the borderline of alexithymia and 34.7% (35/101) patients had not alexithymia. A statistical significant association was observed between alexithymia and inflammatory indeces (ESR: p=0.029, CRP: p=0.043, figure 1 and 2) and also between alexithymia and clinimetrics parameters (ptVAS, pVAS, GH, p<0.0001 for all comparisons). No correlations were observed between alexithymia and disease duration, gender, therapies with bDMARDs. A significant trend has been demonstrated between alexithymia and corticosteroidal therapy Conclusions: This study suggests that alexithymia assessment should be a part of the comprehensive care of patients with RA and PsA. We are in the process of extending this investigation on a larger sample population to improve our investigation field and to consolidate our dates. Disclosure of Interest: None declared